Prediction of the parameters and the hot open die elongation forging process on an 80 MN hydraulic press - Dindorf Ryszard (Open Engineering, 2021)
The main task of the study was to develop and implement predictive control in the hot open die forging process of heavy, large, and hard deformable steel forgings on an 80 MN hydraulic press at the Forged Products Department (FPD) of Celsa Huta Ostrowiec (CHO). The predicted hot flow stresses and the predicted deformation/forging forces as a function of the parameters of the elongation forging process were determined. The predicted parameters of the forging process were included in the dynamic model of the hydraulic forging press. Generalized predictive control (GPC) algorithm of the hot open-die forging process on the hydraulic press was developed. The use of predictive control solved the uncertainty of the hot open forging process, which depends on the dimensions, shapes, and material properties of the forgings, as well as the parameters of the hydraulic press and forging tools.